Chronic granulocytic leukaemia in a patient with chronic renal failure on dialysis. Issue 1 (January 1981) - Dodsworth, H; Gabriel, R
Abstract : A diagnosis of chronic granulocytic leukaemia was made in a man who had been haemodialysed for three years. The association between leukaemia and chronic renal failure is rare.